APPLICATION OF FINANCIAL ACCOUNTING TOOLS SYSTEM ACCORDING TO THE IFRS-9 STANDARD AND ITS ROLE IN IMPROVING THE QUALITY OF ACCOUNTING INFORMATION (APPLIED STUDY IN A SAMPLE OF FINANCIAL COMPANIES LISTED IN THE IRAQ STOCK EXCHANGE) - Nawal Harbi Radhi (Journals Park Publishing, 2023)
The research aims to address the theoretical framework of the IFRS-9 and to indicate the extent to which it can be applied in the financial companies listed in the Iraq Stock Exchange, and to indicate the role that this standard for improving the accounting data and information quality, and thus working decisions to prevent the occurrence of financial crises in a manner that is commensurate with the developments and changes that accompanied the work environment of financial companies. The research was applied in a sample of financial companies listed on the Iraq Stock Exchange for the years 2019, 2020, 2021. The research conclusions of the IFRS-9 standard is considered one of the most important accounting standards in manner international and financial reporting preparation, and it is the standard that includes the financial instruments standard, the requirements for recognition, measurement, impairment in value, exclusion and general hedge accounting, and this standard is related to the accounting treatment of the management activities risks It mainly works on measuring financial assets and liabilities by classifying and measuring assets.